2015
DOI: 10.1037/xhp0000040
|View full text |Cite
|
Sign up to set email alerts
|

Spatial learning while navigating with severely degraded viewing: The role of attention and mobility monitoring.

Abstract: The ability to navigate without getting lost is an important aspect of quality of life. In five studies, we evaluated how spatial learning is affected by the increased demands of keeping oneself safe while walking with degraded vision (mobility monitoring). We proposed that safe low-vision mobility requires attentional resources, providing competition for those needed to learn a new environment. In Experiments 1 and 2 participants navigated along paths in a real-world indoor environment with simulated degraded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 43 publications
1
47
2
Order By: Relevance
“…The difference between this value and the actual angle to the landmark was determined, and the absolute value of the non-reflex angle (the angle < 180°) of this difference was used as a measure of unsigned pointing error. Two participants were excluded because their average error exceeded 90°, again in line with Rand et al (2015).…”
Section: Verbal Pointing Taskmentioning
confidence: 86%
See 2 more Smart Citations
“…The difference between this value and the actual angle to the landmark was determined, and the absolute value of the non-reflex angle (the angle < 180°) of this difference was used as a measure of unsigned pointing error. Two participants were excluded because their average error exceeded 90°, again in line with Rand et al (2015).…”
Section: Verbal Pointing Taskmentioning
confidence: 86%
“…We measured learning at every level of spatial knowledge (i.e., landmark, route, and survey), in addition to testing the participants' awareness of details in their environment via a non-spatial memory test. We chose tasks that have been shown to reflect landmark knowledge (i.e., a landmark recognition memory task; Wenczel, Hepperle, & von Stülpnagel, 2017), route knowledge (i.e., drawing the guided route on an outline of the building; Labate, Pazzaglia, & Hegarty, 2014), and survey knowledge (i.e., a verbal pointing task, indicating angular direction between landmarks; Rand, Creem-Regehr, & Thompson, 2015). We also chose tasks that simultaneously tapped into multiple levels of spatial knowledge, including filling in a building outline with the name and location of learned landmarks and navigating a novel shortcut between two landmarks (Labate et al, 2014).…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The visual restrictions included mild and severe blur, and field restriction. Previous studies have shown that moderately severe blur (in the range 20/500 to 20/800) has little impact on the perceived distance of visible objects [ 6 , 7 ], but does affect learning of spatial layouts [ 8 , 9 ]. In our study, subjects wore blurring goggles that artificially reduced acuity to Snellen 20/135 (Mild Blur) and 20/900 (Severe blur).…”
Section: Introductionmentioning
confidence: 99%
“…Not only is it difficult for them to accomplish daily tasks, it is unsafe and often frightening for them to navigate space; fear and resultant injury are often seen in their processes of wayfinding . This is evidenced by a 2015 study indicating that wayfinding with a vision impairment requires more focused attention on a task and results in a lower tolerance for distractions than when persons are fully sighted (Rand, Creem‐Regehr, & Thompson, ). Reduced mobility, as noted, is tied to fear of injury when navigating unfamiliar spaces (Evans et al, ).…”
Section: Introductionmentioning
confidence: 99%